Characteristics of palm oil clinker as replacement for oil palm shell in lightweight concrete subjected to elevated temperature - Jumaat, Mohd Zamin; Alengaram, Ubagaram Johnson; Ahmmad, R.; Bahri, S.; Islam, A.B.M.S. (Elsevier, 2015)
This article reports the effects of elevated temperature resistance capacity of palm oil clinker (POC) at elevated temperatures; POC was used to replace oil palm shell COPS) as coarse aggregate in oil palm shell concrete (OPSC). The replacement of OPS with POC was done to enhance the performance of concrete before and after exposure when subjected to evaluated temperature. A series of concrete mixes was prepared with 25%, 50%, 75% and 100% replacement of OPS with POC as coarse aggregate in OPSC and the specimens were subjected to elevated temperature of up to 500 degrees C for a period of 30 min and 60 min. Thermogravimetric analysis (TGA) was carried out to check the elevated temperature resistance capacity of OPS and POC. In addition, weight loss, residual compressive strength, colour change in the concrete, cracking on the surface of concrete specimens and ultrasonic pulse velocity (UPV) of OPSC were evaluated at elevated temperatures. TGA analysis shows OPS aggregate loses about 63% of its weight when exposed to temperatures between 285 degrees C and 478 degrees C; however, POC aggregate showed excellent elevated temperature resistance as there was insignificant weight loss of less than 1%. The results of OPSC specimens subjected to 500 degrees C for a period of 60 min showed the number of cracks decreases with the increase of POC content and subsequently the crack width also decreases from 0.319 mm to 0.122 mm. The residual compressive strength loss of specimens with 100% OPS was found as 76% when exposed to 500 degrees C for a period of 60 min and this loss reduces gradually with the increase in POC content; hence at 100% OPS replacement with POC, the loss of compressive strength of only 9% indicates vast improvement of OPSC using POC. Moreover, with the increase in the duration from 30 min to 60 min exposure at 500 degrees C, the loss of concrete compressive strength and UPV values was found higher. (C) 2015 Elsevier Ltd. All rights reserved.